IMAGE PIXEL BASED GRAPHICAL PASSWORD AUTHENTICATION - Geetha Prathibha, O. Sri Harshitha, P. Likitha, P. S. Mani Deepthi, P. Likitha Sai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Authentication dependent on passwords is utilized generally in applications for security and protection. Still, human actions, as an example, choosing bad passwords and contributing passwords in square measures are viewed as "the most fragile connection" in the Authentication chain. Maybe than discretionary alphanumeric strings, clients will pick passwords either short or significant for simple memorization. With web applications and versatile applications accumulation, individuals can get to these applications whenever and anyplace with various gadgets. This advancement brings extraordinary accommodation yet, in addition, builds the likelihood of presenting passwords to bear riding attacks. Attackers can notice straightforwardly or utilize outside recording gadgets to gather client’s qualifications. To avoid this sort of issue, we need another method of confirmation. Here, we can choose a graphical authentication method. The image password offers the best approach to sign on that is simpler than recollecting and composing along with simple passwords. You can sign in by tapping the right points or creating the right gestures over an image that you just selected in advance